Masterworks from the Collection of the National Gallery of Canada. - National Gallery of Canada, Ottawa (Vancouver : Vancouver Art Gallery, 1983)
Braque, George ; Cezanne, Paul ; Courbet, Gustave ; Degas, Edgar ; Leger, Fernand ; Monet, Claude ; Pissarro, Camille ; Poussin, Nicolas ; Renoir, Pierre Auguste ; etc.
Masterworks from the Collection of the National Gallery of Canada, The Vancouver Art Gallery, Vancouver, October 15th to December 3rd, 1983. On the occasion of the inaugural opening of the Vancouver Art Gallery.
English
kunstcatalogus